Application of SIBEL (Tutoring System) in Improving Literacy and Numeracy Skills of Grade 5 and 6 Students of SD Negeri Botok for ANBK Exam Preparation - Aprillia Sinda Dinningrum; Laili Arin Ramadhani (Department of Physics, Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Surabaya (UNESA), 2024)
SIBEL (Tutoring System) is a community service program to assist 5th and 6th-grade students of SD Negeri Botok, Karas District, Magetan Regency, in preparing for the ANBK (Computer-Based National Assessment) exam. This program is focused on improving students' literacy and numeracy skills through structured guidance. The purpose of this program is to create a learning awareness environment at SD Negeri Botok, especially for 5th and 6th-grade students, to help 5th and 6th-grade students improve their ability to do literacy and numeracy problems and to help 5th and 6th-grade students prepare well for the ANBK exam. The implementation of the program took place from 4 September to 30 November 2023 and involved the use of pretest and post-test to measure the improvement of students' abilities. The results of the study showed a significant improvement in students' literacy and numeracy skills, as well as the creation of a learning-conscious environment that supports the success of the program. This SIBEL program has proven effective in preparing students for the ANBK exam.